Political liberties and economic development - Sardón, Jose Luis (Universidad del Pacífico, 1996)
This article looks into the connection between political liberties and economic development. The author reviews the arguments of several studies on the subject and concludes that more political liberties are not necessarily beneficial to economic development since they could jeopardize the rights of ownership far more critically than the arbitrariness of governments with the most indifferent of altitudes to the will of the people. Indeed, "excessive" liberties could favor the interests of private lobbies -and unnecessary State intervention in the economy- or, in unjust societies, lead to the application of moderate or extreme redistribution-oriented policy.